PERILAKU STRUKTUR TOWER TRANSMISI TIPE SUSPENSION TERHADAP BEBAN ANGIN - Redaksi Tim Jurnal (Sekolah Tinggi Teknik - PLN, 2018)
The need for electricity supply in Indonesia is getting bigger along with the higher population growth. This gives encouragement to stakeholders to expand infrastructure development in the electricity sector. Nationally, the biggest demand for electricity is industrial sector, followed by household, business, and general sectors. In its application, the tower transmission structure has a major role to distribute the electricity needs in general. Transmission tower structure is classified as Truss structure. The truss frame is a structure consisting of a combination of rods forming triangular structures connected to each other, and encumbered in their joints. With the concept of balance of style and design of the existing code can be determined the capacity of tower and the response of the structure when carrying the primary loads, especially wind loads.